Retrospective analysis of 261 autopsies of penetrating cardiac injuries with emphasis on sociodemographic factors (2023)
Penetrating cardiac injuries (PCIs) are highly lethal and several factors are related to its incidence and mortality. While most studies focus on characterizing patients who arrived at a medical facility alive and exploring the relationship between the degree of heart compromise and mortality, our study delved deeper into the topic. This study analyzed 261 autopsy reports from 2017 in Bogotá, Colombia, and characterized the factors surrounding PCI incidence and mortality while emphasizing the role of sociodemographic variables. Of these cases, 247 (94.6%) were males with a mean age of 29.19?±?9.7 years. Weekends, holidays, and late hours had the highest incidence of PCIs. The victims' deaths occurred at the scene in 66 (25.3%) cases, and 65.1% of the victims died before receiving medical care. Upon admission, patients with vital signs were more likely to have been transported by taxi or a private vehicle. Two or more compromised cardiac chambers, increased time of transportation, trauma occurred in the city outskirts, and gunshot wounds were related to increased mortality. Our data is valuable for surgeons, health system managers, and policy analysts as we conducted a holistic assessment of the anatomical and sociodemographic factors that are closely associated with mortality following a PCI. Surgeons must recognize that PCIs can occur even when the entrance wound is outside the cardiac box. Reinforcing hospital infrastructure in the outskirts and improving the availability, accuracy, and response time of first responders may lead to improved patient mortality rates.